Comparative Analysis of Waiting and Consultation Times in Convenient Care Clinics versus Traditional Family Practice: A Systematic Review - MD, Anwar Alrashed; Mohamed, Hany Ramadan (South Eastern European Journal of Public Health, 2024)
This systematic review aims to evaluate and compare waiting and consultation times between convenient care clinics (CCCs) and traditional family practice physician offices, with a focus on their impact on patient satisfaction and healthcare delivery efficiency. The review synthesizes data from various studies to assess differences in patient waiting times, consultation durations, and overall satisfaction between these two healthcare settings. A comprehensive search of electronic databases including PubMed, Cochrane, Web of Science, and MEDLINE was conducted to identify relevant studies. Data extraction focused on waiting times, consultation times, patient satisfaction, and any variations based on time of day or healthcare setting. The review found that CCCs generally offer shorter waiting times compared to traditional family practices, enhancing immediate access to care. However, consultations in CCCs were typically longer. Patient satisfaction was higher in CCCs due to reduced waiting periods. The study highlights the effectiveness of CCCs in improving access and patient satisfaction, while also indicating the need for a balance between immediate care and the depth of consultations provided. Further research is needed to explore how these findings can inform improvements in healthcare delivery across various settings.